Moving your Eyes to Solution: Effects of Movements on the Perception of a Problem-Solving Task. Issue 8 (August 2014) - Werner, K.; Raab, M.
There is ample evidence suggesting a bidirectional connection between bodily movements and cognitive processes, such as problem solving. Current research suggests that previous movements can influence the problem-solving process, but it is unclear what phase of this process is affected. Therefore, we investigated participants' gaze behaviour in the first phase of arithmetic problem solving with two groups (plus group, minus group) to explore a spatial bias toward the left or the right while perceiving a problem-solving task (the water-jar problem) after two different movements—that is, for the plus group, sorting marbles from two outer bowls into one in the middle, and for the minus group, sorting marbles from the middle bowl to the outer ones. We showed a right shift of spatial bias for the plus and to the left for the minus group in the perception and problem tasks. Although movements affected gaze, the groups did not differ in their overall problem-solving strategies; however, the first correct solutions did differ. This study provides further evidence of sensorimotor effects on problem solving and spatial bias and offers insight into how a two-phase problem-solving process is guided by sensorimotor information.